Radix Puerariae lobatae (Gegen) suppresses the anticoagulation effect of warfarin: a pharmacokinetic and pharmacodynamics study. Issue 1 (December 2016) - Ge, Beikang; Zhang, Zhen; Zuo, Zhong
Abstract Background RadixSalvia miltiorrhiza (Danshen ) and RadixPuerariae lobatae (Gegen ) are used in Traditional Chinese Medicine to treat cardiovascular diseases. However, adverse herb-drug interactions were observed between warfarin and herbal remedies containingDanshen andGegen . This study aims to investigate the pharmacokinetic and pharmacodynamic interactions between warfarin and the different components found inDanshen andGegen . Methods Sixty Sprague–Dawley rats were used to investigate the effects of warfarin (0.2 mg/kg), Danshen (240 or 480 mg/kg) andGegen (240 or 480 mg/kg) both in isolation and combination. The rats in the warfarin andDanshen/Gegen combination groups were given an oral dose ofDanshen orGegen 2 h after being given an oral dose of warfarin. After five consecutive days of treatment, the pharmacokinetic interactions betweenDanshen/Gegen and warfarin were investigated by simultaneously monitoring and comparing the cytochrome P450 (CYP) activities, mRNA and protein expression levels in the livers of the rats from the different treatment groups. The pharmacodynamic interactions were evaluated by monitoring and comparing the vitamin K epoxide reductase (VKOR) activities, mRNA and protein expression levels in the livers of rats from the different groups, as well as the thrombomodulin (TM) activities, mRNA and protein in the lungs of these animals. The rat plasma soluble thrombomodulin concentrations of the different treatment groups were also evaluated. Microsomes incubation, Real Time-Polymerase Chain Reaction and Western blot was applied respectively to study the activity, mRNA expression and protein expression of CYP, VKOR and TM. Results The activities and expression levels of the CYP and VKOR enzymes in the warfarin-Gegen combination groups increased by nearly 30 % (P  = 0.02) compared with the warfarin-alone group, whereas those of TM decreased by almost 25 % (P  = 0.02). The administration ofDanshen did not lead to any changes in the activities or the expression levels of the CYP, VKOR or TM enzymes compared with those of the control group.Gegen induced several warfarin-metabolizing CYP enzymes and neutralized the effects of warfarin towards VKOR and TM. Conclusion Gegen, rather thanDanshen at the same tested dosage, offsets the anticoagulant effects of warfarin by accelerating the phase I liver metabolism of warfarin, as well as increasing the activity, mRNA and protein expression of VKOR while decreasing those of TM.